2014
DOI: 10.4314/ahs.v14i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibacterial, antifungal and modulatory activity of methanol and ethanol extracts of Padina sanctae-crucis

Abstract: Background: Multi-resistant microorganisms such as Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Candida tropicalis e Candida krusei are the main causes of microbial infections. Padina sanctae-crucis is a seaweed often used to check the contamination of ecosystems by materials such as heavy metals, but studies of the antimicrobial activity of the same seaweed were not found. Methods:The tests for the minimum inhibitory concentration and modulation of microbial resistance, with the use of eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This result indicates that these natural products have an effect on strains of the dermatophyte T. rubrum, suggesting that modulatory activity tests should be conducted with other filamentous fungi that are human pathogens. A possible mechanism for the inhibition of microbial growth can be the hydrophobic nature of the constituents of natural products, which can act on the plasma membrane, making it more permeable to antifungal agents and thereby affecting the biochemical apparatus of the respiratory chain and of energy production [52]. β-caryophyllene is a hydrophobic molecule, which presents low molecular weight; these properties facilitate the permeability in the cellular membrane of the fungi, being able to be involved in the mechanism of action of inhibition of Brazilian Archives of Biology and Technology.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that these natural products have an effect on strains of the dermatophyte T. rubrum, suggesting that modulatory activity tests should be conducted with other filamentous fungi that are human pathogens. A possible mechanism for the inhibition of microbial growth can be the hydrophobic nature of the constituents of natural products, which can act on the plasma membrane, making it more permeable to antifungal agents and thereby affecting the biochemical apparatus of the respiratory chain and of energy production [52]. β-caryophyllene is a hydrophobic molecule, which presents low molecular weight; these properties facilitate the permeability in the cellular membrane of the fungi, being able to be involved in the mechanism of action of inhibition of Brazilian Archives of Biology and Technology.…”
Section: Discussionmentioning
confidence: 99%
“…coli, the ethyl acetate was a greater inhibitor of S. aureus and the ethanol extract against S. aureus and P. aeruginosa. Nogueira et al [ 110 ] reported modulation of antibiotic activity between the Padina sanctae-crucis ethanolic and methanolic extracts and E. coli and S. aureus , and a moderate modulatory effect against these microorganisms and P. aeruginosa , Candida tropicalis and C. kruseim. Stabili et al [ 65 ] confirmed the activity against human pathogenic bacteria and yeasts of lipid extracts of one Mediterranean alga with the difussion disk method.…”
Section: Applicationsmentioning
confidence: 99%
“…Such compounds can act on the plasma membrane, causing it to become more permeable to antifungal agents, affecting the mitochondrial respiratory chain and cellular energy production. Thus, this mechanism can occur due to combined action of the antifungals with natural products at subinhibitory concentrations (Nogueira et al, 2014;Tintino et al, 2014). This is the first report of modulatory activity of a standard antifungal drug combined with EOEB.…”
Section: Resultsmentioning
confidence: 85%